2017
DOI: 10.1016/j.gca.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

The influence of critical zone processes on the Mg isotope budget in a tropical, highly weathered andesitic catchment

Abstract: In order to assess the effects of critical zone processes on Mg concentrations and isotopic signatures of tropical streams, we studied a well constrained, highly weathered andesitic volcaniclastic catchment in the Luquillo Critical Zone Observatory, Puerto Rico. Our results indicate that dissolved Mg concentrations and isotope ratios in the regolith pore water are mainly controlled by rain input, with weathering inputs being more important at sites with thinner regolith (2.7 to 0.9 m deep) and at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 114 publications
6
45
0
Order By: Relevance
“…, Chapela Lara et al . ). The most fractionated materials on Earth are found in low‐temperature environments, with the lowest δ 26 Mg values found in carbonates (δ 26 Mg of −5.6‰, Wombacher et al .…”
Section: Reference Materials Studied and Their Chemical Compositionmentioning
confidence: 97%
“…, Chapela Lara et al . ). The most fractionated materials on Earth are found in low‐temperature environments, with the lowest δ 26 Mg values found in carbonates (δ 26 Mg of −5.6‰, Wombacher et al .…”
Section: Reference Materials Studied and Their Chemical Compositionmentioning
confidence: 97%
“…Carbonate precipitation can therefore drive waters isotopically heavy . There is also an added fractionation effect by the formation of silicate secondary minerals, which mainly tend to preferentially take up heavy Mg isotopes, driving rivers waters isotopically lighter (Tipper et al, 2006a(Tipper et al, , 2008(Tipper et al, , 2012aBrenot et al, 2008;Pogge von Strandmann et al, 2008Huang et al, 2012;Lee et al, 2014;Opfergelt et al, 2014;Chapela Lara et al, 2017). Plants also fractionate Mg isotopes with a variable fractionation direction, although with a general enrichment in heavy isotopes (Black et al, 2006;Bolou-Bi et al, 2010.…”
Section: Riverine Magnesiummentioning
confidence: 99%
“…Magnesium is an element directly involved in the carbon cycle, via weathering of Mg-silicates, precipitation of Mgrich carbonates (both dolomites and high-Mg calcites) and the exchange of Ca for Mg at mid-ocean ridges (Holland, 2005). Therefore Mg isotopes have the potential to provide information on weathering (Tipper et al, 2006b(Tipper et al, , 2012aPogge von Strandmann et al, 2008, 2014aFoster et al, 2010;Higgins and Schrag, 2010;Teng et al, 2010;Opfergelt et al, 2014;Chapela Lara et al, 2017). However, the study of global rivers has revealed a large range in dissolved Mg isotope ratios (Tipper et al, 2006a(Tipper et al, , 2008(Tipper et al, , 2010(Tipper et al, , 2012aBrenot et al, 2008;Pogge von Strandmann et al, 2008Wimpenny et al, 2011;Huang et al, 2012;Liu et al, 2014;Teng, 2017;Oelkers et al, 2019a), and it has become clear that, like all major elements, Mg and its isotopes are affected by a wide range of processes.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the δ 26 Mg values of mineral separates has demonstrated variation in δ 26 Mg values which in some cases overlaps with the δ 26 Mg range in carbonate rocks (−5.57 to −0.38 , Teng, 2017), e.g., biotite (−0.40 to +0.44 , Shen et al, 2009;Ryu et al, 2011), chlorite (−1.82 to +0. 40 , Ryu et al, 2011;Pogge von Strandmann et al, 2015;Chapela Lara et al, 2017), clinopyroxene (−0.62 to +0.43 , Pogge von Strandmann et al, 2011;Wang et al, 2012Wang et al, , 2014Hu et al, 2016;Li et al, 2016;Chen et al, 2018;Stracke et al, 2018), and garnet (−1.96 to −0.37 , Wang et al, 2012Wang et al, , 2014Pogge von Strandmann et al, 2015;Hu et al, 2016;Li et al, 2016;Stracke et al, 2018). Within single rock samples, resolvable variation has also been observed e.g., 1.5 between chlorite and hornblende in granite (Ryu et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Within single rock samples, resolvable variation has also been observed e.g., 1.5 between chlorite and hornblende in granite (Ryu et al, 2011). This silicate mineral source variation in δ 26 Mg has only recently begun to be acknowledged as a source of variation in river δ 26 Mg values (Chapela Lara et al, 2017;Kimmig et al, 2018). Given that recent studies of chemical weathering in the Kangerlussuaq area of West Greenland have stressed the role of silicate weathering (Wimpenny et al, 2011;Andrews and Jacobson, 2018), we wanted to test whether silicate mineral variation in δ 26 Mg values could also account for low δ 26 Mg values in river samples from this area.…”
Section: Introductionmentioning
confidence: 99%